From Subjects to Concept Clouds - Why semantic mapping is necessary - THOMAS, HENDRIK (My University, 2008)
To realize the vision of the semantic web it is essential to be able to exchange formal modeled knowledge between applications and humans without loss of meaning. In this paper, we focus on questions relating to meaning, interpretation and subject identity in modern semantic web languages. Based on the semiotic triangle we show that topics as well as RDF resources are symbols, representing concepts and not referents as the common term ?subject? would indicate. A subject can not be represented as a single entity, but rather as a complex and evolving system of different concepts. Based on this insight we explain how the resulting plurality and uncertainness of the interpretation of symbols can be handled using semantic mappings. By defining transformation rules, the exchange and integration of knowledge from different semantic models becomes possible. Concluding we define recommendations and design guidelines for a semantic mapping management system, which is needed to support users and applications in creating, reusing, managing and applying such semantic mappings.
1st International Conference on Knowledge Federation
PUBLISHED
Inter University Centre Dubrovnik, Croatia
Keywords: Knowledge Federation; Topic Maps; Ontologies; RDF; Subjects